Characterisation of the MONDO detector response to neutrons by means of a FLUKA Monte Carlo simulation. (December 2018) - Giacometti, V.; Battistoni, G.; De Simoni, M.; Dong, Y.; Fischetti, M.; Gioscio, E.; Mattei, I.; Mirabelli, R.; Patera, V.; Sarti, A.; Sciubba, A.; Traini, G.; et al.
Abstract: Particle therapy is increasingly used for the treatment of solid tumours, especially when the tolerance of organs at risk for conventional radiotherapy becomes dose limiting. To take full advantage of the particle therapy potential, the beam range in tissues has to be precisely known and the secondary particles production during the treatment has to be accurately characterised, as it can lead to unwanted dose deposition far from the target volume. Secondary neutrons can release a remarkable dose, also far from the tumour, increasing the probability of secondary cancer late insurgence in the patient. Currently, the treatment planning system software used in clinical routine suffer from the lack of high precision data related to the secondary neutron production in particle therapy treatments. The aim of the MONDO (MOnitor for Neutron Dose in hadrOntherapy) project is to develop a tracking detector for secondary neutrons in the energy range of 20 − 400 MeV. Neutrons flux, energy spectra and angular distribution will become experimentally available by tracking the recoil protons produced after two consecutive neutron elastic scattering interactions in a 10 × 10 × 20 cm 3 matrix of scintillating fibres. A Monte Carlo simulation based on the FLUKA code was developed to optimise the MONDO detector layout, define the tracker trigger logic, evaluate the background contamination and possible strategies for its reduction: preliminary results are reported in this manuscript. A 4 × 4 × 4.8 cm 3 detector prototype was tested with protons at the APSS Proton Therapy Centre in Trento (Italy), where calibration and efficiency measurements were performed. Experimental and simulated results were compared. Highlights: Secondary neutrons (abundantly produced during particle therapy treatments) can lead to dose deposition far from the target. The MONDO project aims to develop a detector for secondary neutrons between 20-400 MeV. The MONDO detector was modelled with a Monte Carlo simulation (FLUKA) for optimisation, trigger logic and background studies. A detector prototype was tested with protons at the APSS Proton Therapy Centre in Trento (Italy).